2016
DOI: 10.29063/ajrh2016/v20i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy Mediates the Association between Partner Trust and Condom Usage among Females but not Males in a Kenyan Cohort of Orphan and Vulnerable Youth

Abstract: Continuing gains against incidence of HIV and other unwanted consequences of unprotected sex requires deeper understanding of characteristics of condom usage among sexually active youth. The present study assesses whether partner trust predicts condom usage, and whether potential associations were mediated by general self-efficacy, among a cohort of sexually active adolescents in Meru County, Kenya. We also sought to discover associations between socio-economic status, psychological resilience and partner trus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Partner's desire was another reason for not using condoms: that is consistent with previous research in this area. [42][43][44][45] In another study conducted among female sex workers in Vietnam, the results showed that most customers were reluctant to use condoms and were even willing to pay more in exchange for unsafe sex. 46 In fact, many of female sex workers stated that they were not able to resist the demands of their sexual partner and to obtain his consent and prevent violence they did not use condoms.…”
Section: Discussionmentioning
confidence: 99%
“…Partner's desire was another reason for not using condoms: that is consistent with previous research in this area. [42][43][44][45] In another study conducted among female sex workers in Vietnam, the results showed that most customers were reluctant to use condoms and were even willing to pay more in exchange for unsafe sex. 46 In fact, many of female sex workers stated that they were not able to resist the demands of their sexual partner and to obtain his consent and prevent violence they did not use condoms.…”
Section: Discussionmentioning
confidence: 99%
“…Literature reported that self-efficacy is one of the most significant predictors of condom use. [14][15][16][17][18] According to social cognitive theory, self-efficacy is a central concept in which both outcome and efficacy of expectations are critical in the promotion of health and behavioral change. 19 Bandura 20 defines the term "self-efficacy" as a "judgment of one's capability to accomplish a certain level of performance".…”
Section: Introductionmentioning
confidence: 99%
“…23 Hence, increasing self-efficacy is recommended for improving condom use among young adults. 16,23,24 Several studies showed that self-efficacy for protective behaviors among youth is associated with effective condom use. [25][26][27][28] A study done in America found that higher self-efficacy for condom use was significantly associated with people who were younger, had higher self-esteem, and communicated better with their sexual partner.…”
Section: Introductionmentioning
confidence: 99%
“…The data collection tool was developed by revising related studies ( 7 , 16 , 22 , 25 , 29 ). A semi-structured questionnaire was used to collect the data through face-to-face interviews.…”
Section: Methodsmentioning
confidence: 99%
“…The factors associated with inconsistent condom use were cost, religion perception, alcohol use, perception of diminished sexual satisfaction, low perception risk of STDs, condom fatigue, having a stable sexual partner and emotional fulfillment, mistrust in relationships, gender inequality, perceptions of modesty, and low condom self-efficacy ( 17 – 19 ). Other studies show that self-efficacy is the most important conjecturer of condom use ( 20 – 22 ).…”
Section: Introductionmentioning
confidence: 99%